Modulação das vias de sinalização intracelulares de células imortalizadas do túbulo proximal de rato submetidas a altas concentrações de frutose - Matsumoto, Larissa Emi [UNIFESP] (2017)
For decades, technological advances and improvement in financial conditions associated with a sedentary lifestyle and an increase in the daily caloric intake of the world population, mainly western, resulted in changes in day to day diet balance. These changes include increased consumption of industrialized foods containing fructose, such as artificially sugar-sweetened beverages, desserts and candies. Several studies have demonstrated this monosaccharide may be responsible for cardiovascular and renal diseases, as well as obesity, diabetes, hypertension, dyslipidemia and, consequently, metabolic syndrome (MS). The hypertension induced by high fructose consumption is associated with non-balance of the Renin-Angiotensin System (RAS). It acts as a endocrine system through circulation and can also act locally in several tissues such as liver, heart and kidneys. In the kidney, the proximal tubule (PT) that is the major region of sodium and water re-absorption expresses all of the RAS components. In high fructose ingestion, inflammation has been observed in this region, but it is unclear how Angiotensin II (Ang II) contributes to fructose inflammatory process, as well as which signaling pathways are involved in this process. We hypothesized that high fructose stimulation can increase Ang II concentration in immortalized rat proximal tubule cells (IRPTC), which results in activation of proinflammatory second messengers as mitogenactivated protein kinases, including extracellular-signal-regulated kinases (ERK 1 and 2), as well as changes the transepithelial electrical resistance (TEER) consequently impacting sodium and water transport, and other transductional efectors that leads to fibrosis and oxidative stress.. To verify the ERK 1 and 2 phosphorilation pattern, the cells were treated with high fructose concentrations for further Western blotting analysis (WB). To analyze changes in TEER, IRPTCs were stimulated with high concentrations of fructose, high concentrations of sodium chloride alone (NaCl) and fructose added to NaCl. In addition, changes in protein expression of water channels, aquaporins 1 (AQP1), receptors (AT1R, AT2R, Gq-GNAQ protein coupled receptors), Na+/H+ exchanger (NHE 3), fructose transporters (GLUT 2 and GLUT 5) and Ang II peptide were qualitatively analyzed by immunofluorescence in the same cells and treatments. For an evaluation of the expression of representative genes involved in G protein-coupled membrane receptor (GPCR) signaling pathways, a specific commercial PCR array was used for this pathway. Our results indicate that the group treated with high fructose enhanced phosphorilated ERK 1 and 2 expression. The TEER results showed that voltage in fructose and fructose + NaCl treated cells were significantly modulated compared to the negative (without any treatment) and positive (NaCl) control. Immunofluorescence analysis provided fructose-dependent changes in GLUT2, GLUT5, NHE3 and Ang II protein expression and AQP1 and AT1R protein translocation. PCR array data revealed significant differences in expression of several genes, that may lead to increased oxidative stress, hypertrophy and celular fibrosis. In conclusion, the renal cell response to high fructose concentrations triggers the modulation of sodium and water reabsorption, RAS activation and increase in ERK 1 and 2 phosphorylation through complex intracellular signaling cascades, contributing to the development of several pathologies.